Particle-stabilised foams: an interfacial study - Stocco, Antonio; Drenckhan, Wiebke; Rio, Emanuelle; Langevin, Dominique; Binks, Bernard P. (SOFT MATTER, 2009)
In an attempt to elucidate the remarkable stability of foams generated from dispersions of partially hydrophobic nanoparticles (fumed silica), we present investigations into the static and dilational properties of the gas-liquid interfaces of such dispersions. By relating the dynamic surface tension gamma(t) and the dilational elasticity E measured using an oscillating bubble device, we confirm that the Gibbs stability criterion E > gamma/2 against foam coarsening is fulfilled. We complement these studies using ellipsometry and Brewster angle microscopy, which provide evidence for a pronounced adsorption barrier for the particles and a network-like structure in the interface at sufficiently high concentrations. We observe this structure also in freely suspended films drawn from the same particle dispersions.
Output ID 22003.
Keywords: General Chemistry; Condensed Matter Physics